Anti-TNF-α restricts dengue virus-induced neuropathy. Issue 5 (25th July 2018) - Jhan, Ming-Kai; HuangFu, Wei-Chun; Chen, Yi-Fan; Kao, Jo-Chi; Tsai, Tsung-Ting; Ho, Min-Ru; Shen, Ting-Jing; Tseng, Po-Chun; Wang, Yung-Ting; Lin, Chiou-Feng
Abstract: Proinflammatory TNF-α facilitates dengue virus (DENV) infection in endovascular dysfunction and neurotoxicity. The introduction of TNF-α blocking therapy with Abs is performed to test its therapeutic effect in this study. In DENV-infected mice, TNF-α production in the brain accompanied the progression of neurotoxicity and encephalitis. DENV infection caused the loss of hippocampal neurons with TNF-α expression around damaged regions, and immunostaining showed the induction of apoptosis in hippocampal neurons. TNF-α was expressed in active microglia and astrocytes in DENV-infected mice. TNF-α facilitated DENV-induced neurotoxicity in vitro in murine Neuro-2a cells. Using a currently established encephalitic mouse model in which DENV infection causes progressive hunchback posture, limbic seizures, limbic weakness, paralysis, and lethality 7 days postinfection, we showed that TNF-α transgenic mice represented the progressive disease development and administration of neutralizing TNF-α Ab reduced dengue encephalitis and mortality. These results demonstrate an immunopathogenesis of TNF-α for mediating DENV-induced encephalitis-associated neurotoxicity and that targeting TNF-α can be used as a strategy against dengue encephalitis. Dengue virus infection induces TNF-α expression around the damaged neuronal cells in the brain while TNF-α blockade ameliorates dengue neurotoxicity and encephalitis.